2023
DOI: 10.1007/s10461-023-03986-5
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Uptake of Long-Acting Injectable Pre-exposure Prophylaxis for HIV Prevention for Men Who Have Sex with Men

Abstract: Pre-exposure prophylaxis (PrEP) is a highly effective HIV prevention tool. Long-acting injectable PrEP (LAI-PrEP) offers another opportunity to reduce HIV. However, how at-risk individuals will consider LAI-PrEP over other modes of administration is unclear. We conducted a discrete choice experiment on preferences for PrEP among a sample of N = 688 gay, bisexual, and other men who have sex with men (GBMSM). We analyzed preferences for mode of administration, side-effects, monetary cost, and time cost using a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
(16 reference statements)
2
12
1
Order By: Relevance
“…The most commonly identified barriers include stigma on PrEP users being promiscuous and HIV positive, their sexuality, inadequate information on PrEP, negative attitudes from PrEP providers, daily pill taking, fear of side effects, and inadequate coverage of PrEP. The findings correspond with many studies identifying the aforementioned barriers (Adeagbo et al, 2021;Dean et al, 2023;Klein & Washington, 2020;Pichon et al, 2022;Pingel et al,…”
Section: Discussionsupporting
confidence: 90%
“…The most commonly identified barriers include stigma on PrEP users being promiscuous and HIV positive, their sexuality, inadequate information on PrEP, negative attitudes from PrEP providers, daily pill taking, fear of side effects, and inadequate coverage of PrEP. The findings correspond with many studies identifying the aforementioned barriers (Adeagbo et al, 2021;Dean et al, 2023;Klein & Washington, 2020;Pichon et al, 2022;Pingel et al,…”
Section: Discussionsupporting
confidence: 90%
“…Literature has identified that a majority of MSM do not take PrEP due to fear of unforeseen side effects of PrEP, which might be long-term (Gredig et al, 2016). The cost The availability of PrEP facilitates willingness to use it (Ahouada et al, 2020;Frankis et al, 2016) Availability of PrEP influences its uptake (Ahouada et al, 2020;Chakrapani et al, 2015;Dean et al, 2023;Diabaté et al, 2021;Galea et al, 2011;Kimani et al, 2022;Pelletier et al, 2019) Preference for PrEP to be accessible at MSM networks (Ahouada et al, 2020;Graham et al, 2023;Harawa et al, 2016;Pelletier et al, 2019) Accessibility of IEC material on PrEP increases knowledge and awareness of PrEP (Graham et al, 2023) Inaccessibility to PrEP influences low uptake (Adeagbo et al, 2021;Han et al, 2019;Harawa et al,…”
Section: Screeningmentioning
confidence: 99%
“…Negative attitudes from health care workers (Adeagbo et al, 2021;Graham et al, 2023;Holloway et al, 2017;Patrick et al, 2019) Lack of confidentiality by health care providers (Graham et al, 2023) Mistrust of health system and pharmaceutical companies (Adeagbo et al, 2021;Chakrapani et al, 2015;Holloway et al, 2017;Liu et al, 2017;Philbin et al, 2016) Uncomfortable talking about sexuality or PrEP with health care providers (Holloway et al, 2017;Patrick et al, 2019;Yu et al, 2021) Not accessible or inadequate coverage (Blair et al, 2022;Han et al, 2019;Harawa et al, 2016;Holloway et al, 2017;Kota et al, 2021;Patrick et al, 2019;Pichon et al, 2022) Cost / high pricing of PrEP (Chakrapani et al, 2015;Dean et al, 2023;Emmanuel et al, 2020;Galea et al, 2011;Graham et al, 2023;Gredig et al, 2016;Han et al, 2019;Harawa et al, 2016;Hojilla et al, 2018;Holloway et al, 2017;Kota et al, 2021;Mansergh et al, 2012;Patrick et al, 2019;Pérez-Figueroa et al, 2015;Voglino et al, 2021) Restrictive and complex procedure for drug procurement (Ahouada et al, 2020;Diabaté et al, 2021;Liu et al, 2017) Long distance to PrEP facilities (transport cost)…”
Section: Information-related Factorsmentioning
confidence: 99%
See 2 more Smart Citations